DETERMINATION OF EMPIRIC DEPENDENCES OF MEAN VALUE OF CIRCULATING MOMENT ON A BIT FROM INFLEXIBILITY AND DEMPFINATION OF BORING INSTRUMENT - Мойсишин, Василь Михайлович; Борисевич, Богдан Дмитрович; Гаврилів, Юрій Львович; Смага, Богдан Ігорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For determination of empiric dependences between the mean value of circulating moment on a bit (moment capacity) from one side and parameters of boring instrument (by inflexibility С and dempfination β ) from second one, on a boring stand IFNTOUNG were twelve conducted five series of the researches after a classic plan broken on three groups. For the first group of researches inflexibility of boring instrument was set at eight level – 225, 400, 1000, 1480, 1700, 2100, 2500 and 6000 kN/m, and dempfination was permanent and made 0,1 kN·s/m. For the second group the inflexibility of boring instrument was set at five level – 400, 1480, 1700, 2500 and 6000 kN/m and dempfination also was permanent and made 0,1 kN·s/m. For the third group the inflexibility was permanent and made 225 kN/m dempfination was set at six level 0.1, 40, 50, 70, 80 and 90 kN·s/m. In the interval of dempfination 40-90 kN·s/m was used hydraulic absorber of vibrations (hydraulic spring). For comparison of statistical descriptions of the selections with the instantaneous values of circulating moment, got at different levels of inflexibility and dempfination statistical verification of parametric hypotheses was applied. As a result of these researches, the following is set: 1. Reduction of inflexibility of boring instrument multiplies moment capacity regardless of type size of bit on the average on 14-22%; 2. Reduction of dempfination from 90 to 0,1 kN· s/m conduces Tд to the increase. Intensity of Tд increase depends on physical mechanical descriptions of breed. For the changes of dempfination from 90 to 0,1 kN·s/m (in the interval of hardness of breed after the stamp of 1440-2050 MPa) this increase was 42-54%; 3. Probability of existence of empiric correlation dependences T д = f ( C ) and T д = f (β ) exceeds 0,95.